Pengaruh Variasi Post Weld Heat Treatment (Pwht) Terdadap Sifat Mekanik Baja Aisi 1045 Hasil Pengelasan Gmaw: The Effect of Post Weld Heat Treatment (PWHT) Variations on the Mechanical Properties of AISI 1045 Steel from GMAW Welding Results - Dico Martdiansyah; Sudirman Lubis (Universitas Pendidikan Ganesha, 2025)
The paper is written fully in Bahasa Indonesia (except the abstract is written in English) using Times New Roman font type, 12 font size and single row space. The paper size is A4 (21 × 29.7 cm) and the author is recommended not to write more than 10 pages. The main article content covers abstract, introduction, literature review, method, result, and conclusion. Pictures, tables and equations can be included in the article. Top, bottom, and right / left margin of the paper are 2.54 cm, respectively. The number of words in the abstract is around 200 words. The abstract should mention briefly the background, objectives, method, and main conclusions. Following the abstract, write down five keywords for indexing. An unusual abbreviation should be defined clearly after the first mentionThis study examines the effect of Post Weld Heat Treatment (PWHT) on the mechanical properties of AISI 1045 steel, particularly tensile strength and hardness, at various treatment temperatures. The tensile test results show that increasing the PWHT temperature tends to decrease the tensile strength of the material. At 600°C, the tensile strength reached 632.62 N/mm², yield strength 408.08 N/mm², and elongation 5.76%. At 700°C, the tensile strength decreased to 551.89 N/mm², the yield strength increased to 433.74 N/mm², and the elongation increased to 7.45%. Meanwhile, at 800°C, the tensile strength continued to decrease to 518.86 N/mm², the yield strength dropped significantly to 306.35 N/mm², and the elongation decreased to 4.8%. Hardness testing showed that the lowest hardness value occurred at 600°C with Base Metal (200.7 HV), Weld Area (220.4 HV), and HAZ (206.9 HV). Meanwhile, the highest hardness value was recorded at 800°C with Base Metal (214.3 HV), Weld Area (240.3 HV), and HAZ (223 HV). The highest hardness value in the Weld Area was obtained at 700°C (263.5 HV). Overall, the higher the PWHT temperature, the hardness of the material increased, but the tensile strength decreased, indicating an increasing trend in material brittleness. This study confirms that PWHT has a significant effect on the mechanical properties of AISI 1045 steel, where the increase in treatment temperature increases hardness but decreases tensile strength. Therefore, the selection of the optimal PWHT temperature needs to be considered to maintain a balance between hardness and toughness of the material in engineering applications.